Climate projections and downscaling techniques - Šmid, Marek (2017)
Šmid, M., & Costa, A. C. (2018). Climate projections and downscaling techniques: a discussion for impact studies in urban systems. International Journal of Urban Sciences, 22(3), 277-307. DOI: 10.1080/12265934.2017.1409132